Navigating financial toxicity in patients with cancer: A multidisciplinary management approach. (18th May 2022) - Smith, Grace L.; Banegas, Matthew P.; Acquati, Chiara; Chang, Shine; Chino, Fumiko; Conti, Rena M.; Greenup, Rachel A.; Kroll, Juliet L.; Liang, Margaret I.; Pisu, Maria; Primm, Kristin M.; Roth, Michael E.; et al.
Abstract: Approximately one‐half of individuals with cancer face personal economic burdens associated with the disease and its treatment, a problem known as financial toxicity (FT). FT more frequently affects socioeconomically vulnerable individuals and leads to subsequent adverse economic and health outcomes. Whereas multilevel systemic factors at the policy, payer, and provider levels drive FT, there are also accompanying intervenable patient‐level factors that exacerbate FT in the setting of clinical care delivery. The primary strategy to intervene on FT at the patient level is financial navigation . Financial navigation uses comprehensive assessment of patients' risk factors for FT, guidance toward support resources, and referrals to assist patient financial needs during cancer care. Social workers or nurse navigators most frequently lead financial navigation. Oncologists and clinical provider teams are multidisciplinary partners who can support optimal FT management in the context of their clinical roles. Oncologists and clinical provider teams can proactively assess patient concerns about the financial hardship and employment effects of disease and treatment. They can respond by streamlining clinical treatment and care delivery planning and incorporating FT concerns into comprehensive goals of care discussions and coordinated symptom and psychosocial care. By understanding how age and life stage, socioeconomic, and cultural factors modify FT trajectory, oncologists and multidisciplinary health care teams can be engaged and informative in patient‐centered, tailored FT management. The case presentations in this report provide a practical context to summarize authors' recommendations for patient‐level FT management, supported by a review of key supporting evidence and a discussion of challenges to mitigating FT in oncology care. CA Cancer J Clin. 2022;72:437‐453.